Синтез нанодисперсных порошков карбидов металлов электровзрывным методом с использованием углеродных наноматериалов - Цолин, Павел Леонидович; Терехов, Анатолий Юрьевич (НТУ "ХПИ", 2015)
Проведены экспериментальные исследования возможности синтеза карбидов металлов электровзрывным методом (в качестве проводника использовали вольфрам и молибден). Установлено, что основным фактором, влияющим на фазовый и дисперсный составы синтезированных наноразмерных порошков карбидов, является отношение выделившейся энергии к энергии сублимации проводника. Показано, что выход насыщенных углеродом фаз и дисперсность карбидов возрастает, а содержание остаточного металла в продуктах взрыва уменьшается с ростом величины энергии.

Processes of synthesis of nanodispersed powders of carbides in the process of electrical explosion of tungsten and molybdenum conductors in the paste containing carbon nanomaterials are experimentally investigated. The paste is obtained by the method of electric discharge treatment of liquid hydrocarbons. It is established that the main factor influencing the dispersed phase and the compositions of the synthesized powders of carbides of tungsten and molybdenum is the ratio of the energy released in a conductor to the energy of conductor’s sublimation. It is shown that the output of carbon-saturated phases and dispersion of carbides increases and the content of residual metal in explosion products decreases with increasing magnitude of input energy.
Synthesis of carbides of molybdenum by electrodischarge method
Keywords: электровзрыв проводников; рентгенофазовый анализ; УНМ; электроразрядная обработка; metal carbides; nanosized carbide powders; x-ray diffraction analysis